Development and validation of a predictive nomogram for subsequent contralateral hip fracture in elderly patients within 2 years after hip fracture surgery - Liang, Jiahui; Zhang, Jian; Lou, Zhiyuan; Tang, Xin (Frontiers in Medicine, 2023)
Purpose Contralateral hip refracture following initial hip fracture surgery is life-threatening in the elderly with high incidence and mortality. This study investigated the associated independent risk factors and established a nomogram prediction model. Methods Totally 734 elderly patients with hip fractures who underwent surgical treatment (January 2016–December 2020) were enrolled. Following analyses on demographic variables, clinical characteristics, and laboratory examination, independent risk factors of contralateral hip fractures in the elderly were identified through the least absolute shrinkage and selection operator (LASSO) regression, and univariate and multivariate logistic regression. Patients were randomly allocated into training (n = 513) and validation sets (n = 221). A training set-based nomogram prediction model was established and assessed for predictability, discriminatory ability, and clinical applicability using the receiver operating characteristic (ROC) curves, calibration curves, and decision curve analysis (DCA) in both sets. Results Contralateral hip refractures occurred in 7.08% (52/734) patients within 2 years after surgery. Age, hemoglobin (Hb), heart disease, neurovascular disease, Parkinson’s disease (PD), Alzheimer’s disease (AD), chronic obstructive pulmonary disease (COPD), and chronic kidney disease (CKD) were independent risk factors. The nomogram prediction model had a favorable discriminatory ability, as indicated by the areas under the ROC curves (AUC): 0.906 (95% CI, 0.845–0.967) in the training set and 0.956 (95% CI, 0.927–0.985) in the validation set. The calibration curves demonstrated a good consistency between the actual subsequent contralateral hip fracture incidence and the predicted probability. The DCA of the nomogram demonstrated the model’s excellent clinical efficacy. Conclusion The nomogram model enabled accurate individualized prediction for the occurrence of subsequent contralateral hip fracture in the elderly within 2 years after surgical treatment, which might help clinicians with precise references for appropriate perioperative management and rehabilitation education following initial hip surgery for their patients.